2023
DOI: 10.3389/fpubh.2023.1118628
|View full text |Cite
|
Sign up to set email alerts
|

Association between composite lifestyle factors and cardiometabolic multimorbidity in Chongqing, China: A cross-sectional exploratory study in people over 45 years and older

Abstract: IntroductionModifiable lifestyle factors are considered key to the control of cardiometabolic diseases. This study aimed to explore the association between multiple lifestyle factors and cardiometabolic multimorbidity.MethodsA total of 14,968 participants were included in this cross-sectional exploratory study (mean age 54.33 years, range 45–91; 49.6% male). Pearson's Chi-square test, logistic regression, and latent class analysis were employed.ResultsWe found that men with 4–5 high-risk lifestyle factors had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Long-term exposure to high level of cortisol may disrupt glucose homeostasis, induce insulin resistance, elevate blood pressure, and increase triglyceride levels, ultimately leading to the development of CMM ( 61 , 62 ). Finally, individuals with obesity often adopt unhealthy lifestyles, including physical inactivity, excessive calorie intake, smoking, and excessive alcohol consumption, all of which are recognized risk factors for CMM ( 63 , 64 ). Our study demonstrated a positive association of CMI, LAP, VAI, and CVAI with CMM, suggesting that these adiposity indicators could potentially serve as simple and effective markers for assessing CMM risk.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to high level of cortisol may disrupt glucose homeostasis, induce insulin resistance, elevate blood pressure, and increase triglyceride levels, ultimately leading to the development of CMM ( 61 , 62 ). Finally, individuals with obesity often adopt unhealthy lifestyles, including physical inactivity, excessive calorie intake, smoking, and excessive alcohol consumption, all of which are recognized risk factors for CMM ( 63 , 64 ). Our study demonstrated a positive association of CMI, LAP, VAI, and CVAI with CMM, suggesting that these adiposity indicators could potentially serve as simple and effective markers for assessing CMM risk.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research on the relationship between nutrition (such as dietary patterns, consumed main foods, nutrient intake) and multimorbidity has been reported in several studies. A cross-sectional exploratory study from China reported that unhealthy dietary behaviors such as over-eating and intra-meal water drinking were linked to an increased risk of cardiometabolic multimorbidity [ 13 ]. Another cross-sectional study conducted in the Netherlands found that adults with cardiometabolic multimorbidity consumed more meat and snacks [ 14 ].…”
Section: Introductionmentioning
confidence: 99%